Sedation effects of intranasal dexmedetomidine combined with ketamine and risk factors for sedation failure in young children during transthoracic echocardiography. Issue 1 (19th November 2018) - Liu, Jianxia; Du, Min; Liu, Lu; Cao, Fei; Xu, Ying
Summary: Background: Sedation is often required for young children during transthoracic echocardiography. Dexmedetomidine and ketamine are two sedatives that are commonly used in children for procedural sedation, but they have some disadvantages when they are used alone. Aims: The aim of this retrospective study was to analyze the effects and safety of intranasal sedation with a combination of dexmedetomidine and ketamine during transthoracic echocardiography in young children and to analyze risk factors for sedation failure. Methods: After IRB approval, we retrospectively evaluated data on patients who underwent echocardiography between May 2016 and August 2017 utilizing a combination of dexmedetomidine 2 μg/kg and ketamine 1 mg/kg. We collected information including heart rate, pulse oxygen saturation, sedation onset time, exam time, recovery time, and adverse reactions. Stepwise logistic regression analyses were performed to analyze the risk factors for sedation failure. Results: Sedation was successful in 2212 patients (96%) and took effect in 15.7 (IQR: 10‐23) min, while sedation failed in 92 patients. Cyanotic heart disease, history of sedation failure, history of congenital heart disease surgery, and fever were independent risk factors for sedation failure. Most of the patients in this study had an American Society of Anesthesiologists (ASA) grade of II to III, but no severe adverse reactions were observed. Conclusion: Intranasal sedation with a combination of dexmedetomidine and ketamine is effective and appears to have an acceptable safety profile for young children during transthoracic echocardiography.